La "non intervention" dans les affaires d'Espagne: documents publies par le Gouvernement de la Republique Espagnole' : [published report] - Delbos, Yvon, 1885-1956 ; Alvarez del Vayo, Julio, 1891 ; Kindeln, Alfredo, 1879-1962 ; Garratt, H. S. ; Patriarca, Vicenzo; Alvaro de Albornoz, Alvaro de, b. 1879
1936-10 015a_0012_005 292/946/15a/12(v)